Late Cretaceous basalts and rhyolites from Shimaoshan Group in eastern Fujian Province, SE China: age, petrogenesis, and tectonic implications. Issue 11 (26th October 2018) - Li, Xi-Yao; Li, San-Zhong; Suo, Yan-Hui; Dai, Li-Ming; Guo, Ling-Li; Ge, Feng-Jian; Lin, Pei-Jun
ABSTRACT: Southeastern China is characterized by an extensive Late Mesozoic (Yanshanian) tectono-magmatic-metallogenic event. Although Late Cretaceous volcanism gradually weakened during the epilogue of the Yanshanian event, its petrogenesis and geodynamic processes remain unclear. In this study, we present new zircon U–Pb–Hf isotopic, whole-rock elemental, and Sr–Nd isotopic compositions data, for volcanic rocks from the Zhaixia Formation of the Shimaoshan Group in Fujian Province. The lower member of the Zhaixia Formation consists of basalts and rhyolites, and the upper member is only rhyolites. These volcanic rocks erupted in the early stage of Late Cretaceous, with basalts erupting earlier (ca. 99–98 Ma) than rhyolites (ca. 98–94 Ma). These basalts record high-K calc-alkaline to shoshonitic, light rare earth element (LREE)- and LILE-enrichment, high field strength element (HFSE)depletion with negligible Eu anomalies, and uniform whole-rock ε Nd ( t ) (–3 to –6) and zircon ε Hf ( t ) (–3.3 to –14.1) values. The overlying rhyolites record peraluminous and high-K calc-alkaline characteristics, LREE- and LILE-enrichment with negative Eu anomalies, and Nb–Ta depletion. The whole-rock ε Nd ( t ) and zircon ε Hf ( t ) values of these rhyolites both increase from the lower member ( ε Nd ( t ), –1.5 to –4.7; ε Hf ( t ), –5.1 to –16.1) to the upper member ( ε Nd ( t ), –0.5 to 0.1; ε Hf ( t ), –0.3 to –4.3). The features imply that these basalts were derived from the partial melting of the enriched lithospheric mantle and the overlying rhyolites from the melting of the crustal components, respectively. Data from the rhyolites in the upper member indicate that more juvenile, Nd–Hf isotopically depleted materials were injected into their source. During the Late Cretaceous, the new, fast rollback of the subducting slab triggered lithospheric extension and asthenospheric upwelling beneath the coastal regions, which induced the melting of lithospheric mantle and crustal components. As continued, the new round of basaltic underplating provided necessary heat to cause partial melting of the deep crust, including the younger, juvenile, and isotopically depleted crustal components.